2009
DOI: 10.1038/hdy.2009.86
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal polymorphism of Drosophila subobscura: a microevolutionary weapon to monitor global change

Abstract: The Palaearctic species Drosophila subobscura recently invaded the west coast of Chile and North America. This invasion helped to corroborate the adaptive value of the rich chromosomal polymorphism of the species, as the same clinal patterns than those observed in the original Palaearctic area were reproduced in the colonized areas in a relatively short period of time. The rapid response of this polymorphism to environmental conditions makes it a good candidate to measure the effect of the global rising of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…Climate strongly influences the genetic constitution of several Drosophila species, such that adaptive polymorphisms (chromosomal inversions) associated with climate have been proposed as tools for monitoring climate change (Umina et al 2005;Balanya et al 2009). Similar associations of adaptive polymorphisms and climate exist in anopheline vectors of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Climate strongly influences the genetic constitution of several Drosophila species, such that adaptive polymorphisms (chromosomal inversions) associated with climate have been proposed as tools for monitoring climate change (Umina et al 2005;Balanya et al 2009). Similar associations of adaptive polymorphisms and climate exist in anopheline vectors of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Montane tropical biota are believed to be particularly vulnerable to global warm ing effects (Sheldon et al 2011). Several longterm studies on Drosophila inversion polymorphisms have shown that changes in inversion frequencies can be a valuable tool to monitor rapid genetic shifts caused by climatic change (Stamenkovic-Radak et al 2008, Balanyà et al 2009, Levitan & Etges 2009; for review see: Rieseberg 2008 andRezende et al 2010). None of these studies, however, addresses the potential effects of climate change on a Drosophila Neotropical species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Drosophila subobscura populations in the New World are estimated to have originated from fewer than and Southern Hemispheres (Huey et al 2000;Pascual et al 2007;Balanyà et al 2009). In this case, despite a strong bottleneck, there appears to have been strong selection for chromosomal inversion frequency and for wing size, both of which show a predictable latitudinal cline in the native range that has developed independently in both northern and southern introduced populations.…”
Section: Genetic Diversity and Niche Breadthmentioning
confidence: 99%